(untitled) (Wallingford, UK, 1996)
The potential role and benefits of agroforestry in sustainable agriculture have been recognized for some time. However, until recently there has been only a limited amount of quantitative physiological evidence to support this. This book breaks new ground in showing how the principles of crop physiology can be applied to the understanding of tree-crop interactions (Syndetic solution)
Keywords: Tree crops,Tree crops,Agroforestry; Physiology,Ecophysiology